The impact of satisfaction with plug-in electric vehicles on future vehicle choice decisions: A hybrid choice modeling framework - Mohammad Maghrour Zefreh; Domokos Esztergár-Kiss (Transportation Research Interdisciplinary Perspectives, 2025)
To boost the market share of plug-in electric vehicles (PEVs) and ultimately achieve 100% of new vehicle sales, it is crucial for early adopters to continue choosing PEVs for their future vehicles. This underscores the importance of understanding who is more likely to be satisfied with PEVs and how this satisfaction impacts their future vehicle choices. This study investigates how satisfaction with the availability of public charging infrastructure, as well as with vehicle and charging technology, influences the future vehicle choices of Hungarian PEV users, utilizing a hybrid choice modeling (HCM) framework. Additionally, this study profiles the PEV users, taking their mobility and sociodemographic characteristics into account, and explores who are more likely to be satisfied with the availability of public charging infrastructure, as well as with vehicle and charging technology, using the structural equation models within the developed HCM framework. The results indicate that satisfaction with vehicle and charging technology as well as with the availability of public charging infrastructure has a positive impact on future PEV choice decisions. Furthermore, the findings reveal that PEV users who frequently charge at work and have a low average daily mileage are more likely to be satisfied with the vehicle and charging technology (e.g., charging time, range) than others. Commuters who use park-and-ride facilities and frequently charge their PEVs there are also more likely to be satisfied with the vehicle and charging technology. Those residing in Budapest who do not use their PEV daily are more likely to be satisfied with the availability of public charging infrastructure. Similarly, PEV users who are willing to walk at least 500 meters from their destination to reach a charging station are more likely to be satisfied with the availability of public charging infrastructure. Moreover, multi-car households and individuals over 40 are more inclined to choose a PEV for their next vehicle. However, household income and university education level did not significantly impact future PEV choice decisions. These insights can assist policymakers in profiling PEV users based on mobility and demographic factors, enabling the formulation of targeted strategies and investments to enhance satisfaction with PEVs and ultimately boost their adoption and market penetration.